A computational analysis of a hypothetical protein from Acinetobacter nosocomialis identifies it as a multicopper oxidase linked to the copper resistance system (Journal of Bangladesh Academy of Sciences, 2025)
Acinetobacter nosocomialis, a nosocomial pathogen, particularly affecting immunocompromised individuals. This species is retaining multidrug resistance and it is increasing over the time. The organism is dependent on human hosts for survival and exerts several methods to circumvent both innate and adaptive immune response. Some of the defence systems are intrigued by extracellular or intracellular proteins of this pathogen. Hence, characterize the unannotated proteins, also called hypothetical proteins, could play a big role in identifying novel treatment targets. In this study, we focused on the characterization of a hypothetical protein (HP) (accession No. KDM58575.1) derived from Acinetobacter nosocomialis. In-silico tools was employed to examine the hypothetical proteins, focusing on physicochemical parameters, subcellular localisation, secondary structure, three-dimensional structure, and functional annotation. To study the active site, protein-protein interactions and molecular docking, the bioinformatics tools CASTp, the STRING server, and PyRx were utilized, respectively. The findings identified this protein as a multicopper oxidase involved in detoxification, transport, and metal binding. The 3D structure derived from the SWISS Model server, and it was matched 89.92% similarity to the AlphaFold DB model A0A0M3ADD5.1, a copper oxidase derived from Acinetobacter sp. AG1 (gene: A0A0M3ADD5_9GAMM). This protein also showed considerable biological activity and consists of five functional domains, like cupredoxin. The proteinprotein interaction also delineates the essential partners required for bacterial viability, whereas KEGG suggested the protein associated with the bacterial two-component signalling system. In docking analysis, the ligand exhibited significant binding activities and suggesting a potential target for treating nosocomials infection. This study highlights the bioinformatics tools for protein characterization and understanding molecular pathways for Acinetobacter nosocomialis. Furthermore, it offers significant insights into the development of innovative therapeutic procedures.J. Bangladesh Acad. Sci. 49(2); 227-242: December 2025